2007
DOI: 10.1103/physrevlett.98.265502
|View full text |Cite|
|
Sign up to set email alerts
|

Monovacancy and Interstitial Migration in Ion-Implanted Silicon

Abstract: The migration of monovacancies (V0) and self-interstitials (I) has been observed in ion-implanted low-doped float-zone silicon by variable-energy positron annihilation spectroscopy. V0 and I were created by the in situ implantation of approximately 20 keV helium ions below 50 K. Monitoring the time evolution of the vacancy response during isothermal heating enabled the measurement of activation energies for I and V(0) [corrected] migration of 0.078(7) and 0.46(28) eV, respectively. In highly As-doped Si, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Our results reveal two well-defined regions in the Arrhenius plot of the DA rate, with very different E a s of 73 and 420 meV, below and above ~60 °C, respectively. A comparison of these E a s with the literature values1112131415 and our rate theory modeling results suggest that inter-cascade communication in Ar-ion-bombarded Si is carried out primarily by migrating interstitials and vacancies, with vacancy migration and interaction being the rate limiting processes.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Our results reveal two well-defined regions in the Arrhenius plot of the DA rate, with very different E a s of 73 and 420 meV, below and above ~60 °C, respectively. A comparison of these E a s with the literature values1112131415 and our rate theory modeling results suggest that inter-cascade communication in Ar-ion-bombarded Si is carried out primarily by migrating interstitials and vacancies, with vacancy migration and interaction being the rate limiting processes.…”
supporting
confidence: 65%
“…With such a large spread in the E a values reported previously2345, the dominant DA processes in Si have remained elusive, with suggestions that the mobile defects in the high-dose regime dominated by inter-cascade DA processes behave differently from the migration of vacancies and interstitials in the low-dose regime of intra-cascade DA effects, commonly monitored by electron paramagnetic resonance (EPR)11, positron annihilation spectroscopy (PAS)12, and deep level transient spectroscopy (DLTS)15. In contrast, our results strongly suggest that, even at relatively high doses and dose rates typical for technologically relevant radiation environments, point defect migration still plays a key role in inter-cascade DA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by the relative lack of movement of any surviving interstitials at the temperatures employed in this study. The VEPAS measurements of [11] showed that the migration energy for silicon interstitials was about five times smaller than for monovacancies (∼0.1 eV), and therefore it is likely that at room temperature all interstitials have migrated to sinks, recombined with vacancies, or formed immobile clusters-playing no further significant role in the vacancy evolution seen here.…”
Section: Resultsmentioning
confidence: 68%
“…By measuring S(E) one can therefore gain semi-quantitative information on the type, concentration and depth profile of vacancy defects in ion-implanted silicon. One can study the formation of vacancy-impurity complexes [7], the evolution of vacancy-type defect structures from divacancies to clusters [8][9][10] and the energetics of vacancy migration [11].…”
Section: Introductionmentioning
confidence: 99%